Green Human Resource Management, Green Transformational Leadership, and Sustainability Performance: The Mediating Roles of Pro-Environmental Behavior and Circular Economy in Batik SMEs - Salsabila, Annisa; Riani, Asri Laksmi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of Green Human Resource Management (GHRM) and Green Transformational Leadership (GTL) on sustainability performance in batik SMEs, with Pro-Environmental Behavior (PEB) and Circular Economy (CE) as mediating variables. Using a quantitative cross-sectional design, data were collected from 155 batik SME owners and employees in Sragen Regency and analyzed using PLS-SEM. The results show that GTL significantly influences PEB, while GHRM strongly affects CE. CE significantly improves sustainability performance and mediates the GHRM–performance relationship, whereas PEB does not mediate these relationships. The findings highlight the importance of structural sustainability mechanisms in enhancing SME sustainability outcomes. Keywords: Green Human Resource Management; Green Transformational Leadership; Circular Economy; Pro-Environmental Behavior; Sustainability Performance; Small and Medium-Sized Enterprises; Resource-Based View; Batik Industry